Right interim and advocacy functions of administrative law: an anthropological dimension - Юринець, Юлія Леонідівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
From the methodological point of law considered anthropology sources of administrative law and justified mainly pravoobespechitelnaya and advocacy functions of administrative law.